Chromosomal abnormalities and structural defects in fetuses with increased nuchal translucency at a Chinese tertiary medical center - Zhang, Huijing; Wang, Shuang; Feng, Chunli; Zhao, Hongyan; Zhang, Weiwei; Sun, Yu; Yang, Huixia (Frontiers in Medicine, 2023)
Objectives To explore the pregnancy outcomes of fetuses with increased NT thickness. Methods This was a retrospective study of fetuses with increased NT (≥95th centile) at 11–14 weeks of gestation between January 2020 and November 2020. Results Among 264 fetuses with increased NT, the median of CRL and NT was 61.2 mm and 2.41 mm. Among them, 132 pregnancy women chose invasive prenatal diagnosis (43 cases of chorionic villus sampling (CVS), 89 cases of amniocentesis). Eventually, 16 cases of chromosomal abnormalities were discovered, including 6 cases (6.4%) of trisomy 21, 4 cases (3%) of trisomy 18, 1 case (0.8%) of 45, XO, 1 case (0.8%) of 47, XXY and 4 cases (3.03%) of CNV abnormalities. The major structural defects included hydrops (6.4%), cardiac defects (3%), and urinary anomalies (2.7%). The incidences of chromosomal abnormalities and structural defects in the NT < 2.5 mm group were 1.3 and 6%, while the incidences were 8.8 and 28.9% in the NT≥2.5 group. Conclusion Increased NT was associated with high risk of chromosomal abnormalities and structural anomalies. Chromosomal abnormalities and structural defects could be detected when NT thickness was between 95th centile and 2.5 mm.